A triboelectric nanogenerator sensor based on phononic crystal structures for smart buildings and transportation systems. (15th June 2022) - Zhu, Lifeng; Zhang, Zhicheng; Kong, Dejuan; Liu, Chengbin; Cao, Zhigang; Chen, Weiqiu; Zhang, Chunli
Abstract: Many buildings and equipment are frequently disturbed by various types of elastic wave or vibration sources in ambient environment. The real-time state monitoring of such a disturbance is very important in the fields of green buildings and intelligent transportation systems. Based on triboelectric nanogenerators (TENGs), we propose a two-dimensional phononic crystal TENG (PC-TENG), which can serve as a self-powered sensor. The PC-TENG system consists of a periodical spherical cavity type of plate-like structure and elastic balls placed in each spherical cavity. Particularly, with bandgap property of phononic crystals, the proposed PC-TENG can also absorb or suppress vibration impact with certain frequencies acting on buildings and equipment. Taking elasticity, diameter, and surface roughness of elastic ball into account, we established a theoretical model of the cavity-ball type of PC-TENG based on Hertzian contact model. The sensing performance of the proposed PC-TENG with 5 by 5 cavities are experimentally measured, which shows the PC-TENG can efficiently detect the amplitude and frequency of an elastic wave disturbance. The theoretical output charges and currents evaluated from the developed theoretical model agree well with the experimental data. Graphical Abstract: ga1 Highlights: A TENG sensor based on phononic crystal structures is proposed. The theoretical model for the proposed PC-TENG incorporating surface roughness and elastic deformation is established. The proposed PC-TENG has a good sensor performance. The surface roughness and material property of elastic ball have an effect on the PC-TENG sensor.